Reconstruction Of Legal Norms As A Regional Head Candidate For Persons With Disabilities With Justice - Putra, Marsudi Dedi (Fakultas Hukum Dehasen, 2025)
The reconstruction of legal norms for people with disabilities as regional head candidates aims to improve regulations to make them more inclusive and fair. This reconstruction includes eliminating discriminatory requirements, such as physical or mental conditions that are not relevant to the ability to perform tasks. In addition, the law should require election administrators to provide reasonable accommodations, such as physical accessibility and technological assistance during the nomination and campaign process. To encourage the involvement of political parties, providing incentives for parties that nominate people with disabilities is also needed. This reconstruction strengthens legal protections for persons with disabilities, supports their political rights, and ensures equal participation in local democratic processes in accordance with the constitution and international commitments, including the Convention on the Rights of Persons with Disabilities.